Kepemimpinan dalam Mengembangkan Religious Culture di Madrasah Aliyah Negeri se-Kota Mataram Nusa Tenggara Barat - S. Ali Jadid Al Idrus (PALAPA, 2022)
Leadership has a very strong relationship with power. Therefore, power has juridical power and can influence others to act as expected. This paper aims to analyze the strategic role of leadership in developing a religious culture. In addition, this paper seeks to explore how leadership can develop a religious culture in Madrasahs, and furthermore to understand the implementation of leadership as an important part in developing a religious culture in State Madrasah Aliyah throughout the city of Mataram. The method used in this paper is qualitative, this approach emphasizes the quality or the most important of social phenomena, events and phenomena. In this study, researchers analyzed social phenomena, phenomena and events regarding the implementation of leadership as part of developing a religious culture in Madrasah Aliyah Negeri in Mataram. Data collection in this study was carried out using in-depth interviews, observation and documentation of the data found in the field. The data analysis of this research uses interactive model data analysis techniques that take place continuously until complete. The analysis takes place simultaneously which is carried out simultaneously with the data collection process, with the flow of stages: (1) data collection (data collection), (2) data reduction (data reduction), (3) data presentation (data display) and (4) conclusions or verification (conclusion drawing and verifying. The results of the research are that Madarsah Aliyah Negeri in the city of Mataram, is a leading educational institution at the secondary education level which is slowly but surely developing a religious culture within their respective madrasah. This can be seen from several activities that the researchers found in the field, for example, the development of a religious culture which is heavily influenced by the policies of the madarsah principal, and this can be seen through (1) the many regulations that are religious in nature that are applied, (2) the religious activities that are routinely carried out by the madrasah. students (3) and the discipline and cleanliness of the study program environment is quite well maintained. (4) the growth of order that reflects harmony and order in the association between madrasa residents, (5) exemplary as part of the leadership orientation in the development of religious culture in Madrasah Aliyah Negeri in Mataram City, and can have implications for instilling students' faith in madrasas. (6) Openness as part of the transparency nature of the school management system and on any issues. The openness of every member of the school is expected to close the existence of mutual suspicion, prejudice, envy, slander and other bad qualities that tend to persecute and damage the rights of others.